Brønsted Acids of Anionic Chiral Cobalt(III) Complexes as Catalysts for the Iodoglycosylation or Iodocarboxylation of Glycals - Wang, Rui; Wu, Wen-Qiang; Li, Na; Shen, Jia; Liu, Kun; Yu, Jie (Synlett, 2019)
Brønsted acids of anionic chiral Co(III) complexes were found to act as efficient phase-transfer catalysts for the diastereoselective iodoglycosylation or iodocarboxylation of glycals with a variety of alcohols or carboxylic acids, respectively, with N-iodosuccinimide as the iodo cation source. The corresponding 2-deoxy-2-iodoglycosides, including monosaccharides and disaccharides, and 2-deoxy-2-iodoglycosyl carboxylates, which are of high synthetic and biological importance, were obtained in high yields (up to 88%) with good diastereoselectivities (up to 9:1 dr).
Keywords: Brønsted acids; phase-transfer catalysis; iodoglycosylation; iodocarboxylation; glycals